Usability Evaluation of Pekanbaru dalam Genggaman Application using System Usability Scale (SUS) - Putera, Thariq Pratama; Angraini, Angraini; Saputra, Eki; megawati, Megawati; Fronita, Mona; Marsal, Arif (Sistemasi: Jurnal Sistem Informasi, 2024)
One of the e-Government applications that has been implemented at the Pekanbaru City Statistics and Information Communication Service is the Pekanbaru Application in Your Hand. This application has been running for approximately 2 years since it was launched on September 2, 2021 and has not undergone any assessment using specific standard methodologies to gauge end-user satisfaction levels. The purpose of this research is to assess the user-friendliness of the Pekanbaru In Hands Application website through the utilization of the System Usability Scale (SUS) method. The SUS method, known for its validity and reliability, offers a straightforward application. It comprises ten questions formulated by John Brooke, and the outcomes are presented as scores ranging from 0 to 100.. The 65 respondents consisted of ASN and non-ASN employees from the Pekanbaru City Communications, Statistics and Informatics Service. The result obtained from the SUS calculation is 59, for the adjective assessment category including ok, with a scale value of F, and including marginally low for the acceptability range category where the application can be accepted but the level of acceptance is still low. This indicates that enhancements are required for the application to achieve a higher acceptance rate. This research produces 4 suggestions for enhancing solutions, serving as valuable references in forthcoming application development.